The Invisible View: Betwixt and Between - Latimer, Christine (Auckland University of Technology, 2008)
This thesis explores the idea of a liminal space, as being dreamlike, suspended in time and physically unlocatable. It questions and exploits the boundary between abstraction and figuration in painting. This investigation has been considered from a subjective viewpoint allowing a distancing of space to illuminate new perceptions and experiences through the language of painting. The project has sought to explore the relationship between the natural world and seeing, to deepen and emphasize the other worldliness of an in-between space. This third space has been evoked by a process of abstracting pictorial content, juxtaposition of elements, colour and composition. The thesis is constituted of practice-based 80%, accompanied by an exegesis 20%.
Keywords: Elusivity of the liminal; Aspects of the impression; Discordant colour; The in-between; Sensed via glimpses; Imagined sites